Analysis of leadership styles in Croatia - Ana Udovčić; Željko Požega; Boris Crnković (Ekonomski Vjesnik, 2014)
During the last two decades, leadership has become the focus of intense interest and research by scientists and theorists. A large number of leadership models have been developed in order to define and enable a certain level of business flexibility that is crucial for survival in a new business environment characterized by frequent market changes, growing global competition and technology development together with demographic changes of employees. This paper aims to determine the dominant leadership style in organizations in Croatia. For the purpose of this paper, empirical research was conducted with the goal of defining the leadership styles of top and middle management of 205 active organizations in Croatia. The research was based on the leadership model developed and established by Rensis Likert. An analysis of leadership styles variables showed that there is a distinguished leadership style in organizations in Croatia. Furthermore, there is an empirically distinguished leadership style concerning the size of the organizations, ownership type and the branches of activity of the organizations in Croatia.